Predicting the threat of shareholder activism among Indian firms: development and application of shareholder activism prediction model. (25th September 2020) - Islam, Ajaz Ul; Mishra, Sanjay Kumar; Srivastava, Vikas
Investigating voting strategies of mutual fund companies, the study developed shareholder activism prediction model (SAPM). Binary panel probit model was used to test the hypothesised model on a sample of firms subjected to shareholder activism (SA) during the period of 2008-2009 to 2014-2015 in India. The SAPM model was found to be adequate. Specifically, governance, related party transactions, remuneration and corporate social responsibility related specific demands were found to significantly predict the probability of threat of SA faced by the sample firms. Subsequently, SAPM model was applied to predict the probability of threat of SA for a sample of S&P BSE 500 companies in India. The findings were utilised to predict the probability that at least one firm in the industry will be subjected to SA for the period FY 2013-2014 to 2015-2016. The predictive accuracy of the model was tested using the observed data for the same period. The findings of binary panel logit model validated the robustness of SAPM.